Antecedents of Perceived Business Performance Among Private Business Organizations: A Partial Least Square Approach - Zahir Osman; Noral Hidayah Alwi; Bibi Nabi Ahmad Khan; Rose Ruziana Samad (Ridwan Institute, 2022)
This study aims to assess the direct relationships between corporate image, employee engagement, organizational culture, employee loyalty, and business performance among private business organizations. This study is vital to be carried out because many private organizations face difficulty to maintain their business performance in the coming years. The research model of this study consists of three independent variables: corporate image, employee engagement, organizational culture, employee loyalty as a mediator, and business performance as a dependent variable. Primary data were utilized in this study and a survey questionnaire which was adopted and adapted from previous studies was used for data collection. 329 clean data were used in the data analysis by utilizing the structural equation modeling technique. Initially, the convergent validity was evaluated on the measurement model by assessing the construct reliability and validity. Then, the discriminant validity was assessed and confirmed through cross-loading and Hetrotrait-Monotrait (HTMT) ratios. Subsequently, the structural model was assessed and the hypotheses testing reveals that corporate image, employee engagement, and organizational culture, have a positive and significant influence on employee loyalty and business performance was strongly affected by employee loyalty.